Zulu Men's Conceptions, Understanding, and Experiences of Voluntary Medical Male Circumcision in KwaZulu-Natal, South Africa. Issue 2 (March 2020) - Nxumalo, Celenkosini Thembelenkosini; Mchunu, Gugu Gladness
Voluntary Medical Male Circumcision (VMMC) is proven to reduce transmission of HIV/AIDS. Despite concerted efforts to scale up VMMC in men aged 18–49, the number of medically circumcised men in this age group remains suboptimal. Research has shown that several individual factors hinder and promote uptake of VMMC. The nature of these factors is not clearly understood within the dimensions of religion, culture and tradition, particularly in a low-income rural setting. This study aimed to analyze Zulu men's conceptions, understanding and experiences regarding VMMC in KwaZulu-Natal (KZN), South Africa. A qualitative phenomenographic study approach was used to collect data from 20 uncircumcised males at six different clinics that provide VMMC services. Ethical approval to collect data was obtained from the Biomedical Research Ethics Committee of the University of KZN (BREC – BE627/18). Individual in-depth face to face interviews were conducted using a semistructured interview guide. Audiotapes were used to record interviews which were transcribed verbatim and then analyzed manually. The conceptions regarding medical circumcision appeared to be related to religious and cultural beliefs surrounding circumcision and the historical traditional practice thereof. The understanding of males regarding VMMC was mainly attributed to HIV prevention; however, knowledge on the degree of partial protection appeared to be limited. An array of negative accounted in the form of complications such as poor wound healing and postoperative pain undergone by peers and other close influencers' accounted for participants' experiences of VMMC. Poor knowledge and negative experiences relating to VMMC could account for reasons why men choose not to undergo VMMC.